(untitled) (Journal of Comparative Social Work, 2015)
The framework for assessment in child protection, as well as the context of the welfare state, differs between England and Norway. Assessments in England are structured in terms of a set model (the triangle) and procedures to be followed, whereas in Norway there are few national guidelines and not a set model for assessments. This underpins professional judgement as the most important component in Norway. This is a study of parents` experiences from assessment in these two contexts, and patterns and themes of assessment experiences have been identified in the two countries through a narrative analysis of in-depth interviews with parents. When asked about their opinions of the current assessment framework, parents in both countries talk more about feelings than about framework and procedures, as their experiences of assessment are similar in both countries. First and foremost, they experience strong emotions in a stressful situation, including anxiety, frustration and powerlessness, but also relief. These cross-national emotions might provide information about how assessment is a stressful situation for the parents involved. However, we find some differences in the way social work is acted out according to the national assessment framework and policy context. In England, the framework and procedures seem to provide clarity with regard to process and power within the system. In Norway, the assessment is characterized by a professional judgement accompanied by more resources, which we find enables helpful decisions from a family perspective. However, this heavy reliance on relationships using professional judgement might also be viewed as a source of informal power. These findings are discussed in relation to theories of emotions and the concept of power. Regarding implications for practice, we would recommend a more explicit awareness of help and control in assessment among social workers involved, together with a clear communication on the topic of emotions and power in assessment.